(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article analyzes some characteristics of the democratic institutions of the political system of the Republic of Kazakhstan, namely: the institution of state control at various levels of government through the prism of political science. Some theoretical positions are presented regarding the nature of the control activities of state bodies in the Republic of Kazakhstan, which are constituted in the Basic Law on the basis of their interaction and the system of checks. The results of the analysis were a number of practical recommendations for optimizing the state control system in the Republic of Kazakhstan.